Inhibition of interferon-mediated induction of indoleamine 2,3-dioxygenase in mouse lung by inhibitors of prostaglandin biosynthesis. - Sayama, S (1981)
Inhibitors of fatty acid cyclooxygenase such as indomethacin (0.1 mM), phenylbutazone (0.3 mM), and aspirin (1 mM) were found to suppress almost completely the interferon-mediated induction of indoleamine 2,3-dioxygenase in mouse lung slices. However, phenacetin, an anti-inflammatory agent devoid of cyclooxygenase inhibitory activity, and sodium salicylate, a weak inhibitor of cyclooxygenase, were much less active under identical conditions. Glucocorticoids including dexamethasone, betamethasone, and cortisone, all of which are inhibitors of phospholipase A2, blocked induction of the dioxygenase by interferon in the nanomolar range, whereas other steroid hormones, such as aldosterone, testosterone, and 17 beta-estradiol, were all but ineffective. These results suggest that the enzymes phospholipase A2 and fatty acid cyclooxygenase, both of which are essential for the biosynthesis of prostaglandins, play an important role in the induction of indoleamine 2,3-dioxygenase by interferon.